Efficiency Analysis of ERDF and CF Co-financed Programmes Focusing on the Transport in Member States of the European Union - Michal Lukas Melecky (Institute of Economic Research (IER), 2017)
European Union provides financial support to the Member States through various financial tools currently from European Structural and Investment Funds that represent the main instrument of EU Cohesion Policy to sustain territorial development, to increase competitiveness and to eliminate regional disparities. The overall impact of EU Funds depends on the structure of funding and absorption capacity of the country. Efficiency of funding across EU Member States is a fundamental issue for the EU development as a whole. The author considers determining the efficiency of EU Funds as an issue of high importance and therefore this study provides a contribution to the debate on the role of the EU Cohesion Policy in EU Member States. The paper focuses on the territorial effects of selected EU Funds in programming period 2007-2013 in theme of infrastructure through transport efficiency analysis. Efficiency analysis is based on data at country level originating from ex-post evaluation of Cohesion Policy programmes 2007-2013 representing the input and output variables to analyse whether the goal of fostering growth in the target countries have been achieved with the funds provided and whether or not more resources generated stronger growth effects in transport accessibility. Study deals with comparative cross-country analysis, descriptive data analysis and multicriteria approach to Data Envelopment Analysis (DEA) in the form of output oriented BCC VRS model. The study aims at testing several factors in form of two inputs and five outputs, trying to elucidate the differences obtained by the EU Member States in efficient using of the European Regional Development Fund and the Cohesion Fund in transport sector. Paper determines if the countries have been more efficient in increasing their levels of competitive advantages linked with transport. Preliminary results reveals that mostly countries with lower amount of funding achieve higher efficiency, especially from the group of EU15.
Keywords: C67; O11; O52; R11; R12; 330; DEA; Efficiency; European Regional Development Fund; Ex-post evaluation; Cohesion Fund